Fresno County Bar Association Annual Bar Banquet at TorNino's - Watkins, Howard::::::::: (1988)
Clockwise from women in blue: Carol Mills, Hagop Bedoyan, Gerald Tomassian, Mary Hoagland , David Jenkins, Susan Coberly, John ?, and ?